Zur Relativierung von Fortschritt in der neueren Sprachwissenschaft - Bzdęga, Andrzej Z (Studia Germanica Posnaniensia, 2018)
The author takes a relativistic stand on the progress in recent linguistic research, starting from the positivistic school of Neogrammarians. As evaluation criteria methodological aspects have been applied, such as immanence and autonomy, reference to diachrony and tradition, modernization of formal and technical instrumentarium, finally some ethic tenets. As unquestionable elements of progress the author recognizes: 1st the opening for new interdisciplinary fields of research, 2nd the overcoming of the scientistic separation of the research object and the research subject (the speaker-hearer himself).